Transient Elastography and Controlled Attenuation Parameter (CAP) in the Assessment of Liver Steatosis in Severe Adult Growth Hormone Deficiency - Carvalho-Furtado, Adriana Claudia Lopes; Carvalho-Louro, Daniela Mariano; Regattieri, Neysa Aparecida Tinoco; Rodrigues, Marcelo Palmeira; Montenegro, Maria Luiza Ricardo Nogueira; Ferro, André Metzker; Pirangi, Patrícia Souza; Naves, Luciana Ansaneli (Frontiers in Endocrinology, 2019)
Non-alcoholic fatty liver disease (NAFLD) is common in patients with growth hormone deficiency (GHD). Some noninvasive techniques have been used to quantify liver fat, such as the controlled attenuation parameter (CAP). Objective: To evaluate CAP as a tool to identify liver steatosis and its relationship with different clinical and biochemical metabolic parameters in a group of patients with severe adult growth hormone deficiency (AGHD), and to compare the evolution of metabolic profiles after 6 months of human growth hormone (rhGH) replacement therapy in a subgroup of patients. Methods: Cross-sectional observational study at baseline of naive rhGH multiple pituitary hormonal deficiency (MPHD) hypopituitarism patients. A 6-month intervention clinical trial in a selected group of a non-randomized, non-controlled cohort was also applied. Results: Liver stiffness measurement (LSM) was normal in severe AGHD patients. CAP evaluation showed steatosis in 36.3% of baseline patients (8/22), associated with higher BMI, waist circumference, insulin, and alanine aminotransferase (ALT) levels. According to steatosis degree by CAP, child-onset growth hormone deficiency (CO-GHD) was graded as 68.75% (11/16) S0, 12.5% (2/16) S1, and 18.75% (3/16) S3, whereas AO-GHD was graded as 50% (3/6) S0, 16.66% (1/6) S2, and 33.33% S3. After 6 months of hrGH replacement, CAP measurements did not change significantly, neither on group without hepatic steatosis at baseline (194.4 ± 24.3 vs. 215.4 ± 51.3; p = 0.267) nor on the group with hepatic steatosis (297.2 ± 32.3 vs. 276.4 ± 27.8; p = 0.082). A significant improvement of body composition was observed only in the first group. Conclusions: We have demonstrated the importance of CAP as a non-invasive tool in the liver steatosis identification on hypopituitary patients. This method may be an important indicator of the severity of metabolic disorders in MPHD patients. In our study, no liver health modification in LSM at baseline or after 6 months of rhGH replacement was found. Longer studies can help to establish the potential repercussions of growth hormone replacement therapy on liver steatosis.